Penggunaan Metode ABCD untuk Peningkatan Partisipasi Masyarakat di Desa Tandon Sentul - Ahmad Qusairi; Berlian Tahta Arsyillah; Khairul Anwar; Ahmad Yakup (Universitas Islam Internasional Darullughah Wadda'wah, 2025)
This study analyzes the implementation of the Asset-Based Community Development (ABCD) approach to increase community participation in the lecturer community service program in Tandon Sentul Village. The main problem often encountered is low community involvement, therefore this study examines the potential of ABCD as a strategy that focuses on utilizing local assets rather than focusing on problems. This study used qualitative methods. Data were collected through observation, interviews, and documentation to understand the real conditions and potential in the field. The results show that the implementation of ABCD successfully increased community participation, making them more active in program planning, implementation, and evaluation. This asset-based program proved relevant and sustainable because it built on existing strengths within the community. Despite challenges such as limited capital and differences of opinion, the program's success opens up opportunities for replication in other villages and the development of local products through digital marketing. Thus, the ABCD approach not only provides a short-term solution but also opens up sustainable economic opportunities for the community.